2008
DOI: 10.1183/09031936.00062707
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of serum albumin antioxidant properties in obstructive sleep apnoea syndrome

Abstract: Antioxidant counteraction of oxidative stress has been poorly explored in obstructive sleep apnoea (OSA). Serum albumin is a major antioxidant agent and structural modifications induced by glucose or free radicals impair its antioxidant properties.The aim of the present study was to compare antioxidant capacities and structural changes of albumin in nonobese OSA patients and healthy volunteers.Albumin structural changes were studied by quenching of fluorescence in the presence of acrylamide. Albumin thiols and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 31 publications
1
29
0
1
Order By: Relevance
“…In the same study, continuous positive airway pressure (CPAP) treatment normalised total antioxidant status [23]. In 2008, impairment of albumin antioxidant properties independent of body mass index (BMI) and related only to OSA severity has been demonstrated [24].…”
Section: Intermittent Hypoxia a Major Stimulusmentioning
confidence: 88%
“…In the same study, continuous positive airway pressure (CPAP) treatment normalised total antioxidant status [23]. In 2008, impairment of albumin antioxidant properties independent of body mass index (BMI) and related only to OSA severity has been demonstrated [24].…”
Section: Intermittent Hypoxia a Major Stimulusmentioning
confidence: 88%
“…This reflects the impaired anti-oxidant HSA activity, which is associated with the enhanced glycation level of HSA in patients affected by this sleep disorder (Faure et al, 2008b). 7.…”
Section: Anti-oxidant Activity Of Human Serum Albuminmentioning
confidence: 99%
“…37 Faure et al demonstrated a decrease in albumin antioxidant properties in non-obese OSA patients when compared with control subjects. 38 Thus, it is highly probable that the increased oxidative stress under reduced antioxidant capacity may have resulted in more severe coronary microvascular injury in the present OSA patients.…”
Section: Nakashima H Et Almentioning
confidence: 99%